The Saburo Hasegawa Reader (University of California Press, 2019)
Published on the occasion of the 2019 exhibition "Changing and Unchanging Things: Noguchi and Hasegawa in Postwar Japan," The Saburo Hasegawa Reader encompasses a selection of writings by the Japanese artist, theorist, essayist, teacher, and curator Saburo Hasegawa (1908-1957), translated into English for the first time. Credited with introducing abstract art to Japan in the 1930s, Hasegawa also became influential as a lecturer on Japan and its aesthetic and philosophical traditions in New York and San Francisco before his premature death in 1957. A memorial volume, initiated by the Oakland Art Museum but left unpublished since the 1950s, as well as interviews from students at California College of Arts and Crafts, helps to establish Hasegawa as a thoughtful bridge between East and West and an engaging and thoughtful interpreter of classical and contemporary sources.